2016
DOI: 10.1080/19490976.2016.1190073
|View full text |Cite
|
Sign up to set email alerts
|

Composition and function of the pediatric colonic mucosal microbiome in untreated patients with ulcerative colitis

Abstract: Inflammatory bowel diseases (IBD) are chronic intestinal inflammatory disorders characterized by a complex disruption of the physiologic interaction between the host immune system and intestinal microbes precipitated by environmental factors. Numerous observations indicate the altered composition and function of the intestinal microbiome of patients with ulcerative colitis (UC), a subtype of IBD. The accuracy of these results may be limited by confounding factors, such as concurrent medication use. To address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 64 publications
(93 reference statements)
5
51
0
Order By: Relevance
“…Although there has been debate over the degree of dysbiosis in paediatric patients, particularly at the mucosal level, most studies have shown substantial differences between diseased and healthy individuals 34,35 . Thus, dysbiotic changes were described in stool and mucosal biopsies from newly diagnosed, treatment-naive children with Crohn's disease, suggesting that dysbiosis might precede clinical disease and develop independently of long-standing inflammation and/or medical therapy 36 .…”
Section: Microbiota Composition and Ibdmentioning
confidence: 99%
“…Although there has been debate over the degree of dysbiosis in paediatric patients, particularly at the mucosal level, most studies have shown substantial differences between diseased and healthy individuals 34,35 . Thus, dysbiotic changes were described in stool and mucosal biopsies from newly diagnosed, treatment-naive children with Crohn's disease, suggesting that dysbiosis might precede clinical disease and develop independently of long-standing inflammation and/or medical therapy 36 .…”
Section: Microbiota Composition and Ibdmentioning
confidence: 99%
“…Characteristic compositional changes observed in patients with IBD include decreased bacterial diversity, with expansion of putative aggressive groups (such as Proteobacteria, Fusobacterium species, and Ruminococcus gnavus ) combined with decreases in protective groups (such as Lachnospiraceae, Bifidobacterium species, Roseburia, and Sutterella) (Table 1) 4, 6, 10, 13, 6973 . This dysbiosis is present at early stages of disease progression, before patients have been treated, but is affected by prior use of antibiotics 61, 69, 73 .…”
Section: Microbiota In Development and Progression Of Ibdmentioning
confidence: 99%
“…Infection agents and chronic inflammation are also known to affect epigenetic states. For example, the maternal microbiome and the postnatal gut microbiome seem to play a role in modulating intestinal mucosal epigenetic patterning and consequent susceptibility to inflammatory bowel disease (IBD) and young‐onset colorectal cancer . Another example is the epigenetic field cancerization observed in gastric cancer, where chronic inflammation induced by Helicobacter pylori is responsible for aberrant DNA methylation .…”
Section: Risk Factors Associated With Epigenome Deregulation and Cancermentioning
confidence: 99%